2020
DOI: 10.1021/acsabm.0c00671
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin Microneedle Patches for the Sustained Release of Levonorgestrel

Abstract: The sustained release of levonorgestrel, a contraceptive, from silk-based microneedle patches was demonstrated for transdermal delivery. Modifications in the formulation of the silk protein and drug loading enabled the tuning of drug loading and release rates from the microneedle patches over time. Sustained drug release reached up to 100 days when the drug was loaded directly inside the microneedles, while release continued for more than a year when the drug was loaded inside microparticles prior to casting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…Published studies have demonstrated that MNs have much potential for delivery of long-acting contraceptives. Yavuz et al [ 329 ] have investigated the silk fibroin-based MN for levonorgestrel sustained release. They found that MN containing levonorgestrel was able to deliver the drug up to 100 days.…”
Section: Current Trend and Prospective Applications Of Microneedlesmentioning
confidence: 99%
“…Published studies have demonstrated that MNs have much potential for delivery of long-acting contraceptives. Yavuz et al [ 329 ] have investigated the silk fibroin-based MN for levonorgestrel sustained release. They found that MN containing levonorgestrel was able to deliver the drug up to 100 days.…”
Section: Current Trend and Prospective Applications Of Microneedlesmentioning
confidence: 99%
“…Transdermal administration is a local route of drug delivery that avoids degradation of the drug in the gastrointestinal tract [ 163 ]. For the transdermal administration of the drug, SF-based structures such as microneedles have been used [ 145 , 164 ]. Microneedles are produced by using numerous methods, including micromolding, soft lithography [ 164 ], photolithography, droplet-born air blowing, solvent casting, continuous liquid interface production, and dipping [ 137 ].…”
Section: Silk-based Biomaterials For Drug Delivery In Cancer Treatmentmentioning
confidence: 99%
“…Moreover, similar to other silk-based material formats, they offer mild aqueous processing conditions, biocompatibility, controllable biodegradation, and robust mechanical properties that are sufficient to penetrate the skin for the delivery of pharmaceuticals followed by degradation and excretion from physiological environments [ 15 , 155 ]. The most frequently explored approaches using silk-based composite microneedles are transdermal vaccines [ 165 , 166 ] and contraceptive delivery [ 145 ]. However, in a study by Gao et al, silk fibroin microneedles were capable of transporting the loaded doxorubicin and photothermal compound across the skin without causing pain [ 137 ], which holds future promise for the delivery of a broad range of biomolecules in cancer therapies.…”
Section: Silk-based Biomaterials For Drug Delivery In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Microneedles (MNs) are medical devices containing microscopic needle shaped projections that can be applied to the skin to deliver a wide range of therapeutics in a minimally invasive, painless, and safe manner [21][22][23][24] . Biodegradable polymer MNs are able to facilitate controlled release of the therapeutic cargo 25 and therefore could be exploited for the release of hormonal contraceptives over extended periods of time (≥1month) [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%